Assessing the Impact of Various Decontamination Instruments on Titanium and Zirconia Dental Implants: An In Vitro Study - Louisa Vierling; Chun Ching Liu; Daniel Wiedemeier; Andrea Gubler; Patrick R. Schmidlin (MDPI AG, 2024)
This study investigates the impact of various instrumentation techniques on material removal and surface changes in titanium (Ti)- and zirconia (Zr) implant discs. Ti- and Zr discs were subjected to standardized experiments using various instruments including airflow, ultrasound, carbide, and diamond burs. Instrumentation was performed for 60 s with continuous automatic motion. Abrasion and changes in surface roughness were assessed using profilometry, while scanning electron microscopy was used to examine morphological changes and particle size. Carbide burs predominantly caused abrasion on Ti discs, while diamond burs caused more abrasion on Zr discs. The Ti discs were more susceptible to surface changes. However, among the materials tested, machined Zr discs treated with diamond burs produced the largest particle. In certain cases, a statistical significance (p < 0.05) was observed between the groups, while in others, there was no considerable difference among the means (p > 0.05). These results highlighted the statistical significance of our findings. These results found diverse alterations in surface characteristics of Ti- and Zr discs due to different instruments, with carbide and diamond burs causing notable effects. The findings highlight the need for a careful balance between promoting healing and minimizing harm during implantoplasty.